The effect of a Division 1 women's basketball strength and conditioning protocol on mental toughness - Olivan, Z.; Cherubini, J. (International Journal of Exercise Science, 2023)
Mental toughness (MT) is a popularized term in sports since it has been found to be positively related to performance. Self-assessment is the most common method of MT data collection. In the strength and conditioning (S&C) context, MT research has focused on males with a notable lack of female participants. Division 1 NCAA strength and conditioning coaches (SCC) spend more hours with their athletes during offseason training than any other coach. The purpose of this study was to measure the perceived effectiveness of an off-season S&C training regimen on MT levels of female athletes while also examining the differences in these perceptions between athletes, teammates, and their SCC. Following a quasi-experimental, longitudinal design, 12 student-athletes assessed their own (n = 58) and one teammate`s (n = 58) levels of MT using the Mental Toughness Index five times over their off-season training S&C regimen. The SCC rated his players, as well (n = 60). MT levels increased significantly post-intervention [F (1, 23) = 7.27, p = .001]. The student-athletes perceived the effect of the intervention as more substantial compared to the SCC [F (1, 117) = 49.03, p < .001]. A more compatible perception of MT was found between athlete and teammate; no statistical significance was observed [F (1, 115) = 1.51, p = .221]. Evidence to support that this off-season S&C program worked regarding increasing MT levels was found. Our findings indicate compatibility between athletes, but not between athletes and coach, in recognizing this construct.